1997
DOI: 10.1359/jbmr.1997.12.9.1378
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Articular Cartilage and Subchondral Bone: Subtle and Progressive Changes in Experimental Osteoarthritis Using 50 MHz Echography In Vitro

Abstract: The main objectives of this work were to demonstrate the potential of 50 MHz echography for assessing initial and progressive morphological and structural changes of articular cartilage and bone developed in an experimental model of osteoarthritis (OA). Degenerative lesions were induced in rat knees by the unilateral intra-articular injection of a 3 mg dose of mono-iodo-acetic acid. To assess the lesion progression, the animals (n ‫؍‬ 30) were sacrificed at different time intervals up to 8 weeks after the inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 19 publications
7
45
1
1
Order By: Relevance
“…Recent research suggests that high-frequency US may also serve ex vivo as a useful means for the investigation of cartilage matrix structural changes occurring under var-ious experimental and clinical conditions (e.g., in the growth process and in osteoarthritis) (9)(10)(11)(12). In particular, our group has shown that 50 MHz US backscatter from cartilage matrix is not sensitive to changes in PG content, but is related to collagen network organization (13).…”
mentioning
confidence: 87%
“…Recent research suggests that high-frequency US may also serve ex vivo as a useful means for the investigation of cartilage matrix structural changes occurring under var-ious experimental and clinical conditions (e.g., in the growth process and in osteoarthritis) (9)(10)(11)(12). In particular, our group has shown that 50 MHz US backscatter from cartilage matrix is not sensitive to changes in PG content, but is related to collagen network organization (13).…”
mentioning
confidence: 87%
“…Initial findings are represented by blurring of the edges, which become irregular and lose their normal sharpness [1,11,17]. Firstly, they involve the superficial cartilaginous margin and correspond to the micro-cleft formation due to tissue deterioration [49]. Later, changes in the echotexture appear, with evidence of loss of homogeneity and transparency [22,[49][50][51][52][53].…”
Section: Us Of the Osteoarthritic Jointmentioning
confidence: 99%
“…Firstly, they involve the superficial cartilaginous margin and correspond to the micro-cleft formation due to tissue deterioration [49]. Later, changes in the echotexture appear, with evidence of loss of homogeneity and transparency [22,[49][50][51][52][53]. With disease progression, focal and asymmetric narrowing is usually present; subsequently, diffuse thinning is charted, up to the complete absence of the cartilaginous layer that corresponds to cartilage breakdown and bony denudation [54][55][56][57].…”
Section: Us Of the Osteoarthritic Jointmentioning
confidence: 99%
“…These investigations have included studies on the assessment of progressive changes in the AC with experimental osteoarthritis (Saied et al 1997), the monitoring of the ultrasound parameters of AC during enzyme digestion (Nieminen et al 2002) and the measurement 5 of the inhomogeneous mechanical properties of AC during compression (Zheng et al 2001(Zheng et al , 2003aFortin et al 2003) (Refer to Zheng et al (2003) for a full list of relevant references). Local strains of AC tissues under compression can be measured or imaged using ultrasound so as to characterize AC in a nondestructive way.…”
Section: Zheng Et Al 2003 Pagementioning
confidence: 99%